2017
DOI: 10.1080/15476286.2017.1279786
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-432 targeting E2F3 and P55PIK inhibits myogenesis through PI3K/AKT/mTOR signaling pathway

Abstract: Skeletal muscle is the dominant executant in locomotion and regulator in energy metabolism. Embryonic myogenesis and postnatal muscle growth are controlled by a cascade of transcription factors and epigenetic regulatory mechanisms. MicroRNAs (miRNAs), a family of non-coding RNA of 22 nucleotides in length, post-transcriptionally regulates expression of mRNA by pairing the seed sequence to 3 0 UTR of target mRNA. Increasing evidence has demonstrated that miRNAs are important regulators in diverse myogenic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 58 publications
1
43
0
Order By: Relevance
“…The specific miRNA in skeletal muscle also regulates the proliferation and differentiation of myoblasts. An analysis of the miRNAs in longissimus dorsi of Rongchang pig revealed that miR‐323‐3p had significant expression changes in different age groups . Furthermore, miR‐323‐3p was highly expressed in muscle.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The specific miRNA in skeletal muscle also regulates the proliferation and differentiation of myoblasts. An analysis of the miRNAs in longissimus dorsi of Rongchang pig revealed that miR‐323‐3p had significant expression changes in different age groups . Furthermore, miR‐323‐3p was highly expressed in muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we performed miRNA sequencing in longissimus dorsi muscle of Rongchang pigs in different age groups. 12 The data showed that miR-323-3p was differentially expressed in two age groups. The present research indicates that miR-323-3p inhibits proliferation and promotes differentiation by targeting Smad2 in myoblasts, and reveals that miR-323-3p functions as a negative regulator in myogenesis.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations